Assessing and Optimizing Traffic Congestion in Muaskar Al-Rashid Highway Interchange in Baghdad - Victor, Tamarah Sameer; Abduljabbar, Ahmed Subhi; Mohammed, Ammar Abbas (Journal of engineering and sustainable development (Online), 2025)
Muaskar AL- Rashid interchange is one of the most important interchanges in Baghdad, where traffic congestion is high during the hours (7:00 - 9:00 am and 1:00 - 3:00 pm). The study aims to ensure maximum traffic safety and capacity on modern highways. Improving the level of service (LOS). Assessing the impact of pedestrians on traffic and their safety during crossing. A set of procedures was used to evaluate the interchange using the VISSIM analysis program and the HCS program to improve the cycle time of traffic signals. Geometric measurements of the intersection were collected using the Geographic Information Systems program (GIS). The results showed LOS  F, and the total number of pedestrians is 1,413. It has been improved through several proposals including geometric redesign of the interchange and implementation of Transportation Demand Management (TDM) strategies, and alteration of the movement of vehicles. The solutions were applied to current traffic volumes and the future after five years. Simulation results show that the reversible route design proposal is more economical and the most appropriate solution. The average travel time is reduced by 81% and the average stop delay is reduced by 80%.